Gender dalam Perspektif QS. An-Nisa Ayat 34 - Devi Rizki Apriliani; Adzkiya Zayyan Mauizah; Dafis Heriansyah; Siti Chodijah; Sholeh Utomo (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to analyze gender in the perspective of QS. An-Nisa verse 34. This research uses a qualitative approach through literature study. The results and discussion of the research show that QS. An-Nisa verse 34 discusses the position of men as the head of the family and shows the portion and role of women and men in the family. This study concludes that QS. An-Nisa verse 34 states the leadership of men in the family. Women and men have their respective roles and portions. More or less QS. An-Nisa verse 34 shows that there are jobs or positions for men that cannot be replaced by women and vice versa. This study recommends other researchers to study gender issues from the perspective of the Qur'an further.